2017
DOI: 10.1016/j.ajo.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Retina and Choroid of Diabetic Patients Without Observed Retinal Vascular Changes: A Longitudinal Study

Abstract: PURPOSE: To identify changes in choroidal thickness (CT) and all retinal layers of diabetic patients without diabetic retinopathy (DR) after 1 year of follow-up. DESIGN: Prospective observational cohort study. METHODS: Overall, 125 diabetic patients without DR were included. Two visits were scheduled: the first visit (V1) and a second visit after 12 months (V2). At both visits, patients received a complete ophthalmologic evaluation that included OCT. Each retinal layer thickness was calculated for 9 ETDRS sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
(33 reference statements)
2
16
0
Order By: Relevance
“…For eyes with these characteristics, a high-penetration OCT with a longer wavelength would be more accurate. Tavares et al [26] observed in their one-year follow-up study that the CT of diabetic patients without DR increased, while the thickness of the inner retinal layers and the total retina decreased, similar to the findings in our research. Several studies have analyzed CT in diabetic patients without DR, although the results have been contradictory.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For eyes with these characteristics, a high-penetration OCT with a longer wavelength would be more accurate. Tavares et al [26] observed in their one-year follow-up study that the CT of diabetic patients without DR increased, while the thickness of the inner retinal layers and the total retina decreased, similar to the findings in our research. Several studies have analyzed CT in diabetic patients without DR, although the results have been contradictory.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Tavares et al looking at choroidal thickening at one-year follow-up, they discuss that the increase in CT observed in DM patients without DR could correspond to the presence of a choroidal vasculopathy, so DME or vascular dilatation with greater rigidity of the blood vessels may be responsible for the increased CT. We found similar results [26]. The autoregulation of the choroid is controversial [31].…”
Section: Discussionsupporting
confidence: 73%
“…Other studies have examined changes in the retinal layers. Tavares Ferreira et al analyzed the outermost layers of the retina in the macular area and found a significant reduction in the photoreceptor layer of DM patients compared to healthy subjects [ 31 ]. Salvi et al [ 9 ] analyzed the GCC in patients with DM2 and healthy individuals and found no differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified alterations in the inner retinal layers of patients without or with minimal DR using structural OCT, suggesting that detectable damage arising from diabetic neuroretinopathy could precede microvascular changes [6,12,13]. On the other hand, other authors reported microvascular changes using OCT-A in patients without DR [6,7,8,9,14,15]. OCT-A represents a relatively new noninvasive way to investigate retinal and choroidal vasculature in details.…”
Section: Introductionmentioning
confidence: 99%